Two Types of Critical Theological Interpretation. (December 2018) - Morgan, Robert
This article challenges a part of the introductory chapter of Biblical Truths in which Dale Martin rejects the nineteenth- and twentieth-century project called New Testament theology, contrasting it with his alternative theological use of the Bible. That contested discipline's characteristic combination of biblical scholarship with the often unspoken religious aims of the interpreters distinguishes it from the explicit theological interpretation of Barth, Martin, the 'biblical theology movement' and most Christian readings of scripture. The latter has priority in churches, but both types are needed for scripture to be a source and norm of faith and theology, and the former is therefore prominent in theological education.